Stock options and chief executive officer compensation - Christopher S. Armstrong; David F. Larcker; Che-Lin Su (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
Although stock options are commonly observed in chief executive o±cer (CEO) compensation contracts, there is theoretical controversy about whether stock options are part of the optimal contract. Using a sample of Fortune 500 companies, we solve an agency model calibrated to the company-specific data and we find that stock options are almost always part of the optimal contract. This result is robust to alternative assumptions about the level of CEO risk-aversion and the disutility associated with their effort. In a supplementary analysis, we solve for the optimal contract when there are no restrictions on the contract space. We find that the optimal contract (which is characterized as a state-contingent payoff to the CEO) typically has option-like features over the most probable range of outcomes.
Keywords: C61; D82; D86; J33; J41; 330; Stock options; incentives; agency model